2013
DOI: 10.7863/jum.2013.32.5.865
|View full text |Cite
|
Sign up to set email alerts
|

Ectopia Cordis in a First-Trimester Sonographic Screening Program for Aneuploidy

Abstract: We review the sonographic features, antenatal course, and perinatal outcomes in 7 cases of ectopia cordis diagnosed in the first trimester. Four cases were associated with a large omphalocele (pentalogy of Cantrell) and 2 with a body stalk anomaly. The remaining fetus had isolated thoracic ectopia cordis. Two pregnancies were terminated; 2 fetuses died in utero; 2 infants died after delivery; and 1 died at 3 months of age. We conclude that the diagnosis of ectopia cordis can easily be established during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…Prenatal diagnosis can be done using qualified and experienced obstetric ultra sonographers as early as 10 weeks of gestation using the traditional two dimensional (2D) imaging sonography; at which stage an omphalocele and ectopia cordis are common findings [ 48 54 ]. While a 3D imaging sonography may be required for the diagnosis of certain fetal anomalies, the diagnosis of pentalogy of Cantrell can sufficiently be made with a traditional 2D imaging sonography [ 49 , 51 , 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis can be done using qualified and experienced obstetric ultra sonographers as early as 10 weeks of gestation using the traditional two dimensional (2D) imaging sonography; at which stage an omphalocele and ectopia cordis are common findings [ 48 54 ]. While a 3D imaging sonography may be required for the diagnosis of certain fetal anomalies, the diagnosis of pentalogy of Cantrell can sufficiently be made with a traditional 2D imaging sonography [ 49 , 51 , 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prenatal sonographic diagnosis of ectopia cordis is relatively easy with two‐dimensional real‐time ultrasound and relies on the demonstration of a pulsating heart outside the fetal chest . Although the prenatal diagnosis in the first trimester has been documented by several authors, the diagnosis before 9 weeks of gestation has not been reported, probably because of the small size of the embryo and the high mortality rate in a significant number of early embryos affected with this condition.…”
Section: Early Sonographic Diagnosis Of Ectopia Cordis: Clinical Casesmentioning
confidence: 74%
“…Apart from the midline anterior ventral wall defect, a defect of anterior diaphragm, a cleft distal sternum, a defect of apical pericardium with communication into the peritoneum, and an intracardiac defect, POC is known to be associated with numerous other anomalies like cleft lip, cleft palate, encephalocele, hydrocephalus, craniorachischisis, thoracoabdominal organ abnormalities include pulmonary hypoplasia, adrenal hypoplasia, gallbladder agenesis, single renal agenesis, polysplenia, malrotation of the colon, herniation of bowel into pericardium, bladder exstrophy, undescended testes and bilateral inguinal hernia, and limb defects include club foot, absence of tibia, radius and hypodactyly [ 3 , 11 ]. The intracardiac anomalies in POC comprise of ventricular septal defects, Ebstein’s anomaly, truncus arteriosus, transposition of great vessels, single atrium, atrioventricular canal, an atrial septal defect, a left ventricular diverticulum, tetralogy of Fallot, a double-outlet right ventricle, and hypoplastic left heart syndrome [ 3 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the thoraco-abdominal variety of ectopia cordis (7% of cases of ectopia cordis), the heart is displaced outside the chest through a defect in the lower sternum in association with diaphragmatic and ventral abdominal wall defects. In the abdominal variety of ectopia cordis (30% of cases of ectopia cordis), the heart is displaced inferiorly into the abdomen through a defect in the diaphragm [ 12 ]. In POC, the sternal defect can be visualized as a partial or complete breach in the continuity of the fetal sternum towards its distal or the lower aspect that can be adequately assessed in the sagittal plane on ultrasound.…”
Section: Discussionmentioning
confidence: 99%